2003
DOI: 10.1034/j.1399-3046.2003.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of pretransplantation cyclosporine pharmacokinetic studies on initial post‐transplantation dosing in pediatric kidney allograft recipients

Abstract: Despite the introduction of a variety of new immunosuppressive agents, cyclosporine A (CsA) has maintained a strong position in pediatric transplantation (Tx). Post-Tx dosing with CsA is a challenging task because of the narrow therapeutic window of the drug, the great individual variability of metabolism and the lack of consensus about the optimal dosage and targeted blood concentration. Sufficient administration of CsA may be protective against acute rejections and other early complications after Tx, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In our center, we have conducted a pretransplantation pharmacokinetic study to identify patients with an exceptionally large or small dose requirement of cyclosporine 52 . In our study, the allometrically scaled systemic clearance immediately after transplantation correlated strongly with the pretransplantation clearance ( r 2 = 0.69), as opposed to the bioavailability, which correlated poorly with its pretransplantation value ( r 2 < 0.01).…”
Section: Discussionmentioning
confidence: 91%
“…In our center, we have conducted a pretransplantation pharmacokinetic study to identify patients with an exceptionally large or small dose requirement of cyclosporine 52 . In our study, the allometrically scaled systemic clearance immediately after transplantation correlated strongly with the pretransplantation clearance ( r 2 = 0.69), as opposed to the bioavailability, which correlated poorly with its pretransplantation value ( r 2 < 0.01).…”
Section: Discussionmentioning
confidence: 91%
“…All patients were on triple immunosuppression consisting of AZA, MP, and CsA (20). Only the microemulsion formulation of oral cyclosporine (Neoral®) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Only the microemulsion formulation of oral cyclosporine (Neoral®) was used. CsA was started with pharmacokinetically determined individual doses (20, 21) three times a day in children under 8 yr of age because of their faster elimination (22) and in two doses in the older children, aiming at a trough blood concentration of 300 μ g/L (specific monoclonal radioimmunoassay). By 3 months after Tx B‐CsA was targeted at 150–200 μ g/L, after 6 months at 150 μ g/L and after 12 months at the maintenance level of 100 μ g/L.…”
Section: Methodsmentioning
confidence: 99%
“…In our opinion, the broad clinical implementation of pretransplantation assessment of CYP3A4 activity with midazolam as a drug probe or pretransplantation tacrolimus pharmacokinetics is not a promising approach because several studies have previously demonstrated clear discrepancies between pre‐ and posttransplantation pharmacokinetics of oral calcineurin inhibitors (CNIs) ( Table 1 ). If pediatric transplant recipients 2 and patients with combination antiretroviral therapy 3 are disregarded, all studies addressing pretransplantation pharmacokinetic assessments with oral CNIs have shown either a poor correlation between pre‐ and posttransplantation pharmacokinetics and dose requirements in “a general” adult kidney transplant recipient population, or that oral CNIs were not superior to standard dosing regimens, or both. Pharmacokinetically, this poor correlation is probably caused by a high within‐patient variability of peritransplant bioavailability of CNIs, 4 but the CNI metabolism will also be affected by the concomitant administration of interacting drugs.…”
Section: Summary Of Studies Investigating Predictive Effect Of Pretramentioning
confidence: 99%